Perlindungan Konsumen terhadap Pelayanan Kesehatan Antara Pasien dengan Tenaga Medis Dokter - Ardiansa Dwi Nanda Putra (Syntax Corporation Indonesia, 2023)
The purpose of this study is to recognize and analyze the bond between doctors and sufferers in the perspective of customer protection law The type of research used in writing this law is normative legal research, with a research approach using legislation, concepts and types of data sources with secondary data and qualitative descriptive data analysis techniques. Discussion: This study examines the relationship between doctors and patients in the perspective of consumer protection law, then about patient losses for medical acts in general, then will review the legal responsibility of doctors from consumer protection in civil terms. Conclusion: There is an asymmetric relationship between doctors and patients, and laws are needed that protect consumers. The responsibility of doctors, which has been regulated in the code of medical ethics, criminal responsibility can arise if it is proven that there are inappropriate acts.